2019
DOI: 10.3892/etm.2019.8372
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the attenuation of chronic inflammatory diseases by aged garlic extract: Involvement of the activation of AMP‑activated protein kinase (Review)

Abstract: AMP-activated protein kinase (AMPK) is an ubiquitously expressed serine/threonine kinase and an important regulator of energy metabolism. The decreased activity of AMPK induced by low-grade chronic inflammation has been implicated in several diseases, including type 2 diabetes and atherosclerosis. However, the activation of AMPK by natural and synthetic products can ameliorate these diseases through the inhibition of inflammation. For example, aged garlic extract (AGE) has been shown to enhance the phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Aged garlic extract suppresses the production of proinflammatory cytokines such as TNF-α and CRP in the liver [37]. In the hypothalamus, aged black garlic (ABG) treatment induced a decrease in leptin receptor (LepR) mRNA levels.…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%
“…Aged garlic extract suppresses the production of proinflammatory cytokines such as TNF-α and CRP in the liver [37]. In the hypothalamus, aged black garlic (ABG) treatment induced a decrease in leptin receptor (LepR) mRNA levels.…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%
“…AMPK is known to phosphorylate the specific serine residue (Ser1177) of eNOS that is essential for its activation (58,59). It was also shown that AGE activated AMPK in both diabetic model TSOD mice (39), and arteriosclerotic model ApoE-KO mice (36). In addition, S1PC enhanced the AMPK activity in mouse spleen cells in vitro (37).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have demonstrated the beneficial effect of AGE on hypertension (8)(9)(10)(11)(12), atherosclerosis (13)(14)(15), metabolic syndrome (16), and gingivitis (17). Furthermore, recent studies have revealed that AGE and its constituents, SAC and S1PC, exert such desirable effects as anti-hypertension (18)(19)(20)(21)(22), cardioprotection (23), antioxidation (24)(25)(26)(27), antiaging (27,28), i m munomodulation (29)(30)(31), a nti-fatig ue (32,33), anti-stress (34,35), anti-inflammation (36)(37)(38)(39), and liver protection (40).…”
Section: Introductionmentioning
confidence: 99%
“…The present study concluded that 12 months of AGE treatment had a lowering effect on the inflammatory biomarker IL-6. AGE has in prior clinical and preclinical studies shown a beneficial effect on inflammation [ 22 , 23 ], with a significant lowering effect on IL-6; however, this is the first time it has been shown to have a lowering effect in a female cohort with a low risk of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…AGE ameliorates atherosclerosis and type 2 diabetes through the suppression of inflammation. AGE modulates the inflammatory response by enhancing the phosphorylation of AMP-activated protein kinase (AMPK) [ 23 ]. AMPK plays an important role in regulating the inflammatory response through the inhibition of the TLR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%